LPI Linux essentials certification exam guide - Tracy, Robb H. (McGraw-Hill Education, 2013)
Complete coverage of the newest exam release from the Linux Professional Institute, and the first step toward LPIC-1 and CompTIA Linux+. Linux Essentials All-in-One Exam Guide covers this "first-of-its-kind" program intended for the academic sector, aspiring IT professionals, and anyone new to the world of Linux and open source technology. This comprehensive, classroom-based reference offers 100% coverage of all exam objectives for the Linux Essentials exam. The book includes expert discussion sidebars to convey in-depth information. Tip, Caution, and Note icons highlight key topics; end-of-chapter quizzes test retention and exam readiness; and Exam Tips guide you through tough technical topics that may be tricky come exam day. The All-in-One also includes hands-on examples and exercises that reinforce practical learning for real-world applicability. Electronic content includes a practice exam (Windows based) and an Adobe Digital Editions e-book (available for download).